2016
DOI: 10.1155/2016/7290686
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Strategies to Modulate the Bone Morphogenetic Protein Signaling Pathway: Current and Future Perspectives

Abstract: Bone morphogenetic proteins (BMPs) constitute the largest subdivision of the TGF-β family of ligands and are unequivocally involved in regulating stem cell behavior. Appropriate regulation of canonical BMP signaling is critical for the development and homeostasis of numerous human organ systems, as aberrations in the BMP pathway or its regulation are increasingly associated with diverse human pathologies. In this review, we provide a wide-perspective on strategies that increase or decrease BMP signaling. We br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 227 publications
0
44
0
Order By: Relevance
“…Misregulation of BMP signaling can cause a variety of disorders in humans (Brazil et al 2015;Salazar et al 2016;Wu et al 2016). Previous studies have demonstrated that BMP signaling can be regulated at many levels, both extracellularly and intracellularly (Bragdon et al 2011;Lowery et al 2016;Sedlmeier and Sleeman 2017). The nematode Caenorhabditis elegans provides a useful system for identifying factors that modulate the BMP pathway.…”
mentioning
confidence: 99%
“…Misregulation of BMP signaling can cause a variety of disorders in humans (Brazil et al 2015;Salazar et al 2016;Wu et al 2016). Previous studies have demonstrated that BMP signaling can be regulated at many levels, both extracellularly and intracellularly (Bragdon et al 2011;Lowery et al 2016;Sedlmeier and Sleeman 2017). The nematode Caenorhabditis elegans provides a useful system for identifying factors that modulate the BMP pathway.…”
mentioning
confidence: 99%
“…Here, we wish to provide a brief outline of strategies currently available to modulate the BMP pathway in vivo, starting from upstream of receptor engagement and moving downstream from receptor and effector activity (Table 2). A greatly expanded discussion of this topic with detailed applications has been published recently (Lowery et al 2016).…”
Section: Current Strategies To Modulate Bmp Pathway Activitymentioning
confidence: 99%
“…Additionally, several BMP-inspired ligands have been developed with enhanced signaling ability compared with naturally occurring BMP ligands (Table 3). Specific applications involve engineered BMP ligands and are highlighted in a recent review (Lowery et al 2016). Delivery of cDNAs encoding these natural or engineered BMP ligands for synthesis in vivo has also been achieved in numerous settings (Lowery et al 2016).…”
Section: Modulation Of Bmp Activity In the Extracellular Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…6). BMPs and activins can be targeted clinically by use of soluble decoy receptors (for a recent 16 review, see (Lowery et al, 2016)). This approach is based on the ligands' affinities to receptor 17 and may not be a specific way of targeting a particular signaling pathway.…”
mentioning
confidence: 99%